Suspicious origin - MacDonald, Patricia (New York : Pocket Books, 2004)
When her estranged sister, Greta, is killed in a fire, Boston news producer Britt Andersen heads straight for her sister's Vermont town where, for the first time, she meets her handsome brother-in-law, Alec Lynch, and her eleven-year-old niece, Zoe -- who narrowly escaped the blaze. Surprised by the bond that she forms with Zoe, Britt stays to help her recover from the tragedy. But when she clashes with her brother-in-law, Britt begins to suspect that her sister's life was far from perfect. Then the deadly fire is declared arson.... To find Greta's murderer, Britt desperately tries to sort truth from innuendo in a close-knit town. But when she uncovers a family secret her sister kept from her, Britt must reexamine her own past -- and face the wrath of a twisted killer who wants her dead.
National College of Business and Arts
Keywords: Arson -- Fiction; Murder -- Fiction; Detective and mystery fiction